Unbroken - Ziegler, Hannah Noel (Cornfield Review, 2020)
If you know me, you probably know that I️ am crazy about writing. I️ began writing when I️ was in elementary school mostly short stories and fantasies, but my poetry craze began last spring, as Dr. Stuart Lishan inspired me to branch out and find my hidden talent. Thus I️ fell in love with the dynamics of poetry, and Unbroken is one of the many works I️ continue to reflect upon. The poem is about my grandfather who was an avid father and tractor salesman, and the legacy he left upon the agriculture community. It serves as a kind of toast to him for also inspiring me to study within the agriculture field.